P7 Radical treatment for lung cancer: impact of recent service improvements. (14th November 2013) - Gornasa, M; Essa, H; Sheikh, H; Shah, R; Taggart, SCO
Abstract : Introduction: The Salford Lung Cancer Service (SLCS) has introduced a number of improvements in care including PET-CT scanning (2005), EBUS (2008), a Northwest Sector MDT for treatment decisions (2009), CPEX testing (2009), IMRT/stereotactic radiotherapy (2011) and development of a surgical high risk MDT (2011). The SLCS holds a data-base of all patients having surgery or radical radiotherapy (DXT) each year since 2000. This study sets out to review our performance for patients receiving either surgery or radical DXT from 2005 to 2012. Methods: The data-base was used in parallel to reviewing each patient record to determine surgical procedure, presence or absence of pre-operative or pre-DXT histology and final tumour stage. For comparative analysis of the effect of these new developments on service delivery, each year was pooled into 2 main groups; Group A (2005–2008) and Group B (2009–2012). Tests for significance were performed using Chi-Squared tables at 5% level. Results: Overall, a total of 178 patients underwent surgery and 138 DXT (See Table). Patients receiving surgery or DXT increased by 62% & 46% respectively from Group A to B although no evidence of any significant change in the proportion of patients having surgery compared with DXT was seen between Group A/B (p = 0.75). Compared with 2005 (n = 18), 29 patients underwent surgery in 2012 (p = 0.08). The proportion of wedge/segmentectomy resections (W/S) doubled over time although this change did not reach significance (p = 0.22). Similar non-significant changes in the proportion of surgical patients with stage 1 disease (p = 0.92), post-operative N2 disease (p = 0.81) and pre-operative histology (p = 0.58) were observed between Group A/B. In contrast, the rate of pre-DXT histology increased significantly from 34% to 65% (p = 0.0007). Overall concordancy between pre-operative and final histology was 97%. In 6 patients not having pre-operative histology, the final diagnosis was malignant neuroendocrine tumour. Conclusions: Improvements in the SLCS over the last 4 years have led to parallel rises in surgical and DXT rates. The rise in surgery numbers likely reflects better patient selection and increase in use of W/S whereas that for DXT appears to be the result of improved diagnostics reflected by significantly higher rates of histological diagnosis.